Advances in the isolation and characterization of milk-derived extracellular vesicles and their functions - Di, Shujuan; Huang, Yibo; Qiao, Weicang; Zhang, Xiaomei; Wang, Yaling; Zhang, Minghui; Fu, Jieyu; Zhao, Junying; Chen, Lijun (Frontiers in Nutrition, 2024)
Milk-derived extracellular vesicles (EVs) have various functions, including immune regulation and promoting intestinal development. These EVs have substantial potential for application in infant formula and functional foods development. In addition, numerous studies have shown that milkderived EVs carry proteins, lipids, and nucleic acids away from their parental cells, acting as messengers between cells. Moreover, structural integrity and biological viability are necessary prerequisites for the functional and omics studies of milk-derived EVs. Therefore, selecting appropriate methods for isolating and characterizing milk-derived EVs is essential for subsequent studies. Accordingly, this review summarizes the isolation and characterization methods for milkderived EVs and their biological functions and roles. Furthermore, it discusses the comprehensive application of isolation methods, providing a reference for research on and development of milkderived EVs.